EKSPLORASI ETNOMATEMATIKA PADA PERMAINAN ENGSET MELAYU SAMBAS DAN APLIKASINYA DALAM PEMBELAJARAN MATEMATIKA - Kurniasari Kurniasari; Halini Halini; Bistari Bistari (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study was to determine the mathematical concepts contained in the Malay Sambas engset game and the relationship between the mathematical concepts and the Malay Sambas engset game and to apply the Malay Sambas engset game in the form of LKPD in mathematics learning in class VIII junior high school in flat shape material. The form of research was qualitative with an ethnographic approach. Data collection tools in the form of a camera, interview guidelines, and observation guidelines. The object of this research was the engset Malay Sambas game in Kubangga village, Teluk Keramat sub-district related to playing tools, playing fields, playing rules, and how to play. The results showed that there were 9 mathematical concepts that exist in the Malay Sambas engset game related to playing tools, playing fields, playing rules, and how to play, namely the concept of flat shape, building space, congruence, reflection, mathematical logic, set, chance, counting, and number pattern.Keywords: Ethnomathematic Exploration, Engset Games, Mathematics Learning